Increasing incidence of hip fracture in Chiang Mai, Thailand - Prasit Wongtriratanachai (2018)
Hip fracture is a major health problem in Thailand. This study attempted to examine the incidence, related factors, and trends of hip fracture in Chiang Mai, Thailand. All hip fracture data among patients aged 50. yr or older were collected from hospitals in Chiang Mai, Thailand from August 1, 2006 to July 3, 2007. Data from the 1997 Chiang Mai hip fracture study were used for comparison. In the study period, 690 hip fractures were reported: 203 males and 487 females (male to female ratio was 1to 2.4), with a mean age of 76.7. yr. The estimated cumulative incidence was 181.0 per 100,000, and the adjusted incidence was 253.3 (males: 135.9; females: 367.9). A simple fall was the most common mechanism (79%) of fracture, and 80% of the hip fractures occurred in patients aged 70. yr or older. The highest incidence of hip fracture was observed in patients older than 85. yr (1239). At 6. mo postfracture, most patients (61%) used a walking aid. Compared with the 1997 data, hip fracture incidence had increased by an average of 2% per yr, and the incidence of hip fracture had increased significantly from August 1, 2006 to July 31, 2007, especially in patients older than 75. yr. In patients older than 84. yr, the incidence increased by a factor of 2. Urgent strategies for the prevention and treatment of osteoporosis, and hence hip fracture, are needed. © 2013 The International Society for Clinical Densitometry.